ParallelGlobal with Low Thread Interactions (Informatica, 2021)
Global is an optimization algorithm conceived in the ’80s. Since then several papers discussed improvements of the algorithm, but adapting it to a multi-thread execution environment is only a recent branch of development [1]. Our previous work focused on parallel implementation on a single machine but sometimes the use of distributed systems is inevitable. In this paper we introduce a new version of Global which is the first step towards a fully distributed algorithm. While the proposed implementation still works on a single machine, it is easy to see how gossip based information sharing can be built into and be utilized by the algorithm. We show that ParallelGlobal is a feasible way to implement Global on a distributed system. However, further improvements must be made to solve real world problems with the algorithm.